1995
DOI: 10.1002/j.1460-2075.1995.tb07186.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct and independent sites on IL-6 trigger gp 130 dimer formation and signalling.

Abstract: The helical cytokine interleukin (IL) 6 and its specific binding subunit IL‐6R alpha form a 1:1 complex which, by promoting homodimerization of the signalling subunit gp130 on the surface of target cells, triggers intracellular responses. We expressed differently tagged forms of gp130 and used them in solution‐phase binding assays to show that the soluble extracellular domains of gp130 undergo dimerization in the absence of membranes. In vitro receptor assembly reactions were also performed in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 37 publications
6
180
1
Order By: Relevance
“…This assumes that the receptors follow the structural pattern that has been observed in the GHR, PRLR, and EpoR, the class 1 cytokine receptors for which structures are known (de Vos et al, 1992;Livnah et al, 1996). For IL-6 and CNTF, such a three-site cytokine/receptor binding model is consistent with mutagenesis data and the finding that the ternary receptor-complexes of IL-6 (Ward et al, 1994b;Paonessa et al, 1995) and CNTF are hexameric (cf. The ternary complex).…”
Section: The Complex Of Growth Hormone and Its Receptorsupporting
confidence: 53%
See 3 more Smart Citations
“…This assumes that the receptors follow the structural pattern that has been observed in the GHR, PRLR, and EpoR, the class 1 cytokine receptors for which structures are known (de Vos et al, 1992;Livnah et al, 1996). For IL-6 and CNTF, such a three-site cytokine/receptor binding model is consistent with mutagenesis data and the finding that the ternary receptor-complexes of IL-6 (Ward et al, 1994b;Paonessa et al, 1995) and CNTF are hexameric (cf. The ternary complex).…”
Section: The Complex Of Growth Hormone and Its Receptorsupporting
confidence: 53%
“…Based on the assumption that the complex formation of IL-6 with its cellular receptors can be mimicked by soluble forms of IL-6R and gp130, we (Ward et al, 1994b) and, more recently, Paonessa et al (1995) showed that IL-6 mediates its actions on target cells through the formation of a hexameric complex comprising two molecules each of IL-6, ILdR, and gp130. While there are models of the formation and topology of the hexameric complex Ward et al, 1996), a detailed understanding of the interactions between IL-6 and its receptor molecules at a highresolution structural level is lacking.…”
Section: Determination Of the Active Sitementioning
confidence: 99%
See 2 more Smart Citations
“…One of the key cytokines is IL-6, which was originally identified as B-cell stimulatory factor-2 and was shown to affect hybridoma growth and also stimulate antibody productivity (Makishima et al 1992). In the proposed mechanism, IL-6 binds to IL-6R and gp130 (Bravo et al 1998;Hibi et al 1990;Muller-Newen et al 2000) to form hexameric complex composed of two molecules of each component (Paonessa et al 1995;Skiniotis et al 2005;Ward et al 1996). This in turn triggers homodimerization and activation of gp130, leading to activation of the Janus kinase family (JAK1, JAK2, TYK2) of signal transducers, which further activate transcription activators (STAT1, STAT3) and mitogen-activated protein kinases (MAP-KKK, MAPKK, MAPK) (Matsuda et al 1999).…”
Section: Introductionmentioning
confidence: 99%